Preoperative Physical Activity Predicts Surgical Outcomes Following Lung Cancer Resection. (March 2021) - Billé, Andrea; Buxton, James; Viviano, Alessandro; Gammon, David; Veres, Lukacs; Routledge, Tom; Harrison-Phipps, Karen; Dixon, Allison; Minetto, Marco A.
Objectives: To assess whether preoperative levels of physical activity predict the incidence of post-operative complications following anatomical lung resection. Methods: Levels of physical activity (daily steps) were measured for 15 consecutive days using pedometers in 90 consecutive patients (prior to admission). Outcomes measured were cardiac and respiratory complications, length of stay, and 30-day re-admission rate. Results: A total of 78 patients' datasets were analysed (12 patients were excluded due to non-compliance). Based on steps performed they were divided into quartiles; 1 (low physical activity) to 4 (high physical activity). There were no significant differences in age, smoking history, COPD, BMI, percentage predicted FEV1 and KCO and cardiovascular risk factors between the groups. There were significantly fewer total complications in quartiles 3 and 4 (high physical activity) compared to quartiles 1 and 2 (low physical activity) (8 vs 22; P = .01). There was a trend ( P > .05) towards shorter hospital length of stay in quartiles 3 and 4 (median values of 4 and 5 days, respectively) compared to quartiles 1 and 2 (6 days for both groups). Conclusions: Preoperative physical activity can help to predict postoperative outcome and can be used to stratify risk of postoperative complications and to monitor impact of preoperative interventions, ultimately improving short term outcomes.